محتويات المعادن الثقيلة (كادميوم، رصاص، نيكل) في التوابل المستوردة - موسى أمين; سلمان فؤاد (Latakia University Journal -Biological Sciences Series, 2019)
The concentrations of some heavy metals such as cadmium (Cd), lead (Pb) and nickel (Ni) in imported spices collected as composite samples from the custom areas of Lattakia seaport hhave been estimated using atomic absorption. The study Has shown differences in heavy metal concentrations according to the origin and kind of spices. The highest concentrations of Ni (3.21, 3.11) in mg/kg dw were recorded in cloves and cardamom, respectively, while highest concentrations of Pb were 0.85, 0.43, 0.42 and 0.35 mg/kg in coriander, nutmeg, pimento and cinnamon, respectively. Cd concentrations were generally below the permissible levels approved by WHO and FAO. The highest concentrations were 0.17 and 0.14 in cloves and black pepper, respectively. The obtained results have shown significant correlations between averages and maximum content of each heavy metal. Correlation coefficient values were 0.844, 0.786 and 0.564 for Cd, Pb and Ni, respectively. Provisional Tolerable Weekly Intake (PTWI) has been calculated for each heavy metal. جرى تقدير تراكيز بعض المعادن الثقيلة الموجودة في توابل مستوردة (جمعت بوصفها عينات مركبة من ضمن المنطقة التابعة لجمارك مرفأ اللاذقية) باستخدام جهاز الامتصاص الذرّي. بيّنت الدراسة تبايناً في تراكيز المعادن الثقيلة تبعاً لمنشأ التوابل ونوعها. سُجّلت التراكيز الأعلى للنيكل (3.21، 3.11 ملغ/كغ مادة جافة) في القرنفل وحبّ الهيل على التتالي، أمّا التراكيز الأعلى للرصاص فكانت 0.85، 0.43، 0.42، 0.35 في الكزبرة، جوزة الطيب، البهار والقرفة على التتالي. كانت تراكيز الكادميوم دون الحدود المسموح بها من منظمة الصحة العالمية ومنظمة الأغذية والزراعة، وقد كانت التراكيز الأعلى للكادميوم 0.17 و 0.14 في كلٍّ من القرنفل والفلفل الأسود على التتالي. أوضحت النتائج وجود علاقة ارتباطية بين المتوسطات والحدّ الأعلى للتركيز. قيم معامل الارتباط كانت 0.844، 0.786، 0.564 لكلٍّ من الكادميوم والرصاص والنيكل على التتالي. وقد جرى حساب المعدل الافتراضي للمتناول أسبوعياً PTWI لكلٍّ من المعادن الثقيلة المدروسة.